EPIDEMIOLOGICAL ASPECTS OF EUTHYROID DIFFUSE GOITER IN A GROUP OF ADULTS WITH THYROID DISEASES AND DIABETES MELLITUS AND OTHER CHANGES IN GLYCEMIC BALANCE - Gherbon Adriana (European Scientific Journal, ESJ, 2015)
Background & aims: thyroid disorders are frequently associated with diabetes in clinical practice. The purpose of this study is to assess the prevalence of euthyroid diffuse goiter (edg) in a group of adults with diabetes mellitus (dm) and other changes in glycemic balance. Methods: the studied group was of 650 people with dm and other changes in glycemic balance, aged between 18 - 79 years. The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters. Results: the prevalence of edg in the study group was 37.84% (38.43% f and 32.25% m, p = 0.34, x2 = 0.91). Edg prevalence in type 1 diabetic group was 1.66% (1.81% f and 0% m, p = 0.76, x2 = 0.09), 43.1% in type 2 diabetic group (44.04% f and 36.84% m, p = 0.4, x2 = 0.7), 44.26% in igt group (43.93% f and 50% m, p = 0.7, x2 = 0.14), and 33.33% in ifg group (35.18% f and 11.11% m, p = 0.14, x2 = 2.17). Significant differences regarding edg prevalence were found between the group with type 1 and type 2 diabetes and other changes in glycemic balance, but not between type 2 diabetes and other changes in glycemic control. Conclusions: there were not significant differences regarding gender in patients with edg and dm or other changer in glycemic balance. We noticed no association with type 1 diabetes (autoimmune disease), but only with dm type 2 and other changes in glycemic balance.